Effect of religious fatalism and concern about new variants on the acceptance of COVID-19 vaccines - Oscar Mamani-Benito; Rosa Farfán-Solís; Mariné Huayta-Meza; Madona Tito-Betancur; Wilter C. Morales-García; Edison Effer Apaza Tarqui (Frontiers in Psychiatry, 2023)
IntroductionTo protect public health, it is important that the population be vaccinated against COVID-19; however, certain factors can affect vaccine acceptance.ObjectiveThe objective of this study was to determine whether religious fatalism and concern about new variants have a significant effect on the acceptance of COVID-19 vaccines.MethodologyAn explanatory study was conducted with 403 adults of legal age captured through non-probabilistic convenience sampling in vaccination centers in the 13 health networks of the Regional Health Directorate of Puno, Peru. Data were collected through a brief scale of religious fatalism, a scale of acceptance of vaccines against COVID-19 and a scale of concern about a new variant of COVID-19.ResultsThe proposed model obtained an adequate fit. There was a negative effect of religious fatalism on vaccine acceptance, a positive effect of fatalism on vaccine rejection, a positive effect of concern about new variants on the acceptance of vaccines, and a positive effect of concern about new variants on vaccine rejection.ConclusionThese findings provide evidence for the usefulness of considering both religious fatalism and concern about new variants affect the intention to receive the COVID-19 vaccine in adults in southern Peru.